Analisis Metafora Konseptual dalam Dongeng Nusantara (Linguistik Kognitif dalam Cerita Anak) - Puspitoningrum, Encil; Santoso, Anang; Martutik (University of Brawijaya, 2026)
This study aims to identify cultural patterns and values in conceptual metaphors found in Nusantara fairy tales using a cognitive linguistic approach. This study was designed as a qualitative-descriptive study with a focus on analysing three main fairy tales that represent geographical diversity, namely Timun Mas from Java, Putri Mandalika from West Nusa Tenggara, and Malin Kundang from West Sumatra. The results of the analysis show that there are a total of 55 conceptual metaphors found in the three fairy tales. Structural metaphors dominate about fifty percent of all findings, followed by ontological and orientational metaphors. These metaphors serve as a means of transmitting cultural values that vary between regions, such as contextual wisdom in the western region, the values of collectivity and sacrifice in the central region, and an emphasis on social harmony and relationship with nature. These findings also reveal the mindset of the Indonesian people, who prioritise collectivity over individuality, as reflected in the metaphorical structure of fairy tales. The conclusion of this study confirms that Nusantara fairy tales are a medium rich in cultural cognition. Pedagogically, this study offers important implications for character education through a story-based moral education approach, where the metaphorical structure in fairy tales can serve as a cognitive scaffold for internalising moral values. Theoretically, this study also enriches the development of cognitive linguistics in the context of Indonesia's multicultural society.